Zmienność otoczenia przedsiębiorstwa a podejście do budżetowania - Wierzbiński, Marcin (The changeability of business environment versus budgeting methods, 2006)
In the article author tries to match different budgeting methods with a degree of business environment changeability. Author claims that the more changeable the business environment the more flexible budgeting methods we need to use. In companies operating, for example, in high technology industries where the business environment is very unstable, it is possible to replace traditional budgeting with other performance measurement like balanced scorecard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 410-417